2021
DOI: 10.1108/jadee-09-2021-0237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on the economy of oil palm smallholder's household income

Abstract: PurposeThis study aimed to determine the impact of the COVID-19 pandemic on the oil palm smallholders' income, which includes both on-farm and off-farm resources.Design/methodology/approachThis study used a simultaneous equations system for arranging the oil palm household economic model.FindingsThe results showed that the negative effect of demand disruption (decreasing of household income) is more than supply disruption (production declining). Declining household income due to COVID-19 caused farmer househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The findings show that the decline in household income (10%) is five times greater than the decline in harvested output (2.23%). The result reinforced what has been shown by Mahmud and Riley (2021) and Irawan et al. (2022) that the demand shock (falling household income) is more dominant in affecting the economy of smallholder farmer households than the supply shock.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The findings show that the decline in household income (10%) is five times greater than the decline in harvested output (2.23%). The result reinforced what has been shown by Mahmud and Riley (2021) and Irawan et al. (2022) that the demand shock (falling household income) is more dominant in affecting the economy of smallholder farmer households than the supply shock.…”
Section: Resultssupporting
confidence: 82%
“…A decrease in farmer household income can also occur due to COVID-19 causing the demand for agricultural labor from outside agriculture to decrease or disappear, which causes sources of income for farmers from outside agriculture to decrease or disappear. Irawan et al. (2022) find out how the demand shock phenomenon is experienced by oil palm smallholder households in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, they underline the increased environmental and health concerns by consumers, which cause a significant orientation to palm-oil free products, even though this seemed to be a decision matured long before the Covid-19 pandemic. Irawan et al (2022), moreover, focused on palm oil industry consequences deriving from Covid-19, in particular they found that demand disruption is higher than supply disruption and the decrease of household income generated the impossibility for farmers to access to basic goods. Not only, the entire supply chain has suffered the pandemic effects (Ivanov and Das, 2020), despite the growing necessity to make it more sustainable (Kasim et al, 2021), as highlighted by Hafiz et al (2022) whose study shed light to the most relevant elements of a palm oil-sustainable supply chain, which are firstly environmental costs, rapidity and adaptability, in particular in a post-pandemic period.…”
Section: Covid Effects On Food Industry and Food Consumptionmentioning
confidence: 99%